Feasibility study of feminist epistemology in Ayatollah Javadi Amoli's epistemological system - zahra khani; Vahid Sohrabifar (حکمت اسرا)
The movement of feminism in the West was born after creating equality and removing the oppression of women in the legal and political system, but with the passage of time, the concern of this movement extended to the epistemological field as well. In feminist epistemology, by breaking the foundation of conventional western epistemology, the natural and social experiences of human beings become important in knowledge, and these experiences determine the epistemic differences of women and men in the form of the influence of sex and gender. Due to the dynamism and attention of Islamic philosophy to the issues of the day, feminist epistemology cannot be ignored by Muslim philosophers, especially a thinker like Ayatollah Javadi Amoli, who, while being comprehensive in various sciences, also pays attention to the issues of the day.The purpose of writing this article is to investigate the possibility of realizing feminist epistemology in the epistemological system of Javadi Amoli, for this purpose, all his documents and works in the field of epistemology and women have been studied with the method of analysis of documentary studies.The results of this research show that by the creation of corporeal and Immortality of spirit as the pillars of knowledge in the epistemology of Javadi Amoli and his belief in the separation between sex and gender in women's studies, we can talk about the influence of sex and gender on credit and functionalist sciences. He said without such influence leading to epistemological relativity.